2008
DOI: 10.2514/1.37464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Humidity on Transonic Flow

Abstract: An experimental investigation of the effects of humidity-induced condensation on shock/boundary-layer interaction has been conducted in a transonic wind-tunnel test. The test geometry considered was a wall-mounted bump model inserted in the test section of the wind tunnel. The formation of a -shape condensation shock wave was shown from schlieren visualization and resulted in a forward movement of the shock wave, reduced shock wave strength, and reduced separation. Empirical correlations of the shock wave stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, depending on the airfoil geometry and heat supply conditions, the pressure drag around the airfoil can be reduced to the classic dry air case at the same Mach number [10,11]. Recently, transonic shock waves-boundary layer interaction over a wall-mounted bump under various humid conditions was investigated experimentally by Huang et al [13]. The formation of a λ-shape condensation shock ahead of the main shock was observed from schlieren visualization.…”
Section: Introductionmentioning
confidence: 99%
“…However, depending on the airfoil geometry and heat supply conditions, the pressure drag around the airfoil can be reduced to the classic dry air case at the same Mach number [10,11]. Recently, transonic shock waves-boundary layer interaction over a wall-mounted bump under various humid conditions was investigated experimentally by Huang et al [13]. The formation of a λ-shape condensation shock ahead of the main shock was observed from schlieren visualization.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for this oscillation has been reasonably explained in a series of experimental studies by Matsuo 1,2) et.al., using a Ludwieg tube. The latent-heat release also influences the accuracy of a Pitot-static tube for Mach number measurements [3][4][5] . Numerical calculations 6) for viscous flow at large subsonic Mach number, have shown that the lift-to-drag ratio is decreased as relative humidity is increased, due to the presence of this condensation shock wave.…”
Section: Introductionmentioning
confidence: 99%